A few words of friendship for Hoshyar Nooshin. Issue 3 (June 2017) - Motro, René
The aim of this paper is to evoke some events that the author shared with Professor Hoshyar Nooshin during more than forty years. Beyond scientific aspects, human relationships constituted the founding of an enthusiastic cooperation.